Analisis perhitungan harga pokok produksi dengan menggunakan metode full costing dan variable costing untuk menentukan harga jual pada UMKM Java Bakery - Kartika, Nadya; Akbar, Aswin (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The purpose of this study was to analyze the calculation of the cost of production of Donuts carried out at Mr. Isak Nasirin's Java Bakery Business. Analyzing the calculation of the cost of goods produced using the full costing and variable costing methods at the Java Bakery business and the differences and their effect on the selling price. The results of data analysis obtained that the calculation of the cost of goods produced by the owner of Java Bakery and using the full costing method has a difference of Rp 326, -,. The results of the calculation of the cost of production have a difference between the variable costing method and what the company does is Rp 322, - and the determination of the selling price based on the calculation of the full costing method is Rp 1,051, - while the variable costing method is Rp 1,047, -, but Java Bakery usually rounds the selling price per pcs to Rp 2,000. The amount of profit expected by the owner wants 50% of the cost of production per pcs of donuts.